Educação e proteção social em um projeto social público : um estudo à luz da sociologia configuracional - Silva, Taiana Valencio da (Universidade do Vale do Rio dos Sinos, 2019)
The present dissertation presents a study about education and social projects. In order to carry out this work, we investigated the configurations that modulate the relationship between education and social protection in the context of a public social project based on a conceptual approach inspired by the Norbert Elias' Configurational Sociology. We used as an investigative itinerary the systematization of a conceptual framework stating a double process of expansion of formative experiences, from school to society and simultaneously from society to school. These movements favored an ethnographic study about the relationship between education and social protection in the context of a social project. The analytical tools used for data interpretation were the notions of configuration and interdependence, from which social relations were understood beyond the antagonisms known in the sociological literature between individual and society, avoiding readings that dichotomize the individual and the social. The data revealed three configurations, namely: (a) the organizational ambivalence between form-design and school-form reaching to understand the relations which are established between the professionals of the protection network and the institutions, as well as, the approximations and distances between social project and school; (b) the definition of students as vulnerable, according to the professionals' perspective, understanding the context and vulnerability relationships that characterize the students from the project; and (c) the work of social educators, analyzing the work of these professionals and their relationships with the social project, based on their experiences of work on others. Thus, we concluded that Projeto Ação Legal configurations intensify the formative process which integrate other social processes, using political, educational and cultural strategies. Through the interlocution between education and social protection, social relations now take the form of pedagogical relationships.
Keywords: Configuração; Projeto social; Educação; Proteção social; Configuration; Social project; Education; Social protection; ACCNPQ::Ciências Humanas::Educação